As origens do pensamento científico segundo Mário Schenberg: elementos junguianos - Sogawa, Flávio Shiungi (2024)
Mário Schenberg, in his book “Pensando a Física”, proposes that one of the possibilities for the origin of scientific ideas is the theory of the Collective Unconscious by the Swiss physician and psychologist C.G. Jung. Jung formulated his theory based on the analysis of his patients' dreams and compared them with elements found in ancient alchemical treatises. Furthermore, in correspondence with Richard Wilhelm, he discovered that many possible answers to his questions were present in a Chinese alchemical treatise linked to Taoism. It is expected that by the end of this work we will be able to establish the relationship between the origin of scientific ideas and Jungian thought on the Collective Unconscious